2021
DOI: 10.1186/s12887-021-02808-8
|View full text |Cite
|
Sign up to set email alerts
|

Parental experience of the neuromotor development of children with congenital heart disease: an exploratory qualitative study

Abstract: Background Children with severe congenital heart disease (CHD) are a group of children at risk for neurodevelopmental impairments. Motor development is the first domain to show a delay during the first year of life and may significantly contribute to parental concerns, stress, and difficulties in early child-parent attachment. Thus, the aim of the study was to better understand the wishes and concerns of parents of children with CHD and explore their experience of their children’s neuromotor de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 48 publications
0
15
0
Order By: Relevance
“…Motor delay contributes to parental concerns and difficulties in child-parent wellbeing. In our qualitative study about the experience of parents of infants with CHD, parents reported that they were reluctant to challenge their infants [31]. They feared over-exerting them and watched them constantly.…”
Section: Parental Engagementmentioning
confidence: 87%
See 3 more Smart Citations
“…Motor delay contributes to parental concerns and difficulties in child-parent wellbeing. In our qualitative study about the experience of parents of infants with CHD, parents reported that they were reluctant to challenge their infants [31]. They feared over-exerting them and watched them constantly.…”
Section: Parental Engagementmentioning
confidence: 87%
“…The PT in turn shares her/his professional and empirical knowledge, clinical reasoning, and current research evidence in early intervention. b Encouragement of parents' confidence and family well-being In our qualitative study, parents expressed the need to strengthen their confidence and learn how to trust their children's abilities [31]. The PT uses different strategies to encourage parents' confidence and family well-being.…”
Section: Partnering With Parents a Parents' Attendance And Active Eng...mentioning
confidence: 98%
See 2 more Smart Citations
“…First, parents of infants with CCHD have major concerns about their infant's motor development and their own tendency to overprotect the child. 32 Second, current approaches in physical therapy use family coaching as a major strategy. The coaching strategy implies that both the infant's vulnerable physical condition and the parental stressful situation are taken into account.…”
Section: Discussionmentioning
confidence: 99%